INOVASI OLAHAN KERIPIK JAGUNG GULA AREN SEBAGAI PRODUK YANG BERNILAI EKONOMIS DI DESA WATANG KASSA - Sariana Damis; Fitriyani Syukri; Fatimah Fatimah; Muhammad Aljabar; Nurfardianty A.R.Amrah (Universitas Muhammadiyah Sidenreng Rappang, 2024)
This research aims to develop an innovative corn chips product using palm sugar as a natural sweetener, which is expected to increase the economic value of local products in Watang Kassa Village. The village is known for producing corn and palm sugar, but the potential of these two ingredients has not yet been fully utilized as commercial processed products. This innovation is expected to provide product diversification, increase local community income, and create broader market opportunities. The research methods used include field studies, recipe trials, and market analysis. The results of the study show that corn chips with palm sugar not only have a unique flavor and are well-received by consumers, but also have great market potential as a regional specialty product. With this innovation, corn chips with palm sugar can become an economically valuable product that contributes to improving the welfare of the people in Watang Kassa Village.